Malnutrition screening in patients admitted to hospital with an exacerbation of chronic obstructive pulmonary disease and its association with patient outcomes. Issue 4 (7th August 2016) - Law, Stephanie; Kumar, Praneel; Woods, Sharon; Sriram, Krishna B
ABSTRACT: Objectives : There is a paucity of information on the prevalence and clinical implications of malnutrition in patients hospitalised for management of acute exacerbations of chronic obstructive pulmonary disease (AECOPD). This study aimed to fill this gap in knowledge. Methods : We performed a retrospective observational cohort study of 100 hospitalised AECOPD patients. The Malnutrition Screening Tool (MST) was used to identify patients at risk of malnutrition (MST ≥2). Patient characteristics, length of stay, readmission rate, 12-month survival and overall survival were collected using a proforma. Results : MST scores were available in 90 patients, of whom 22% of patients had a MST score of ≥2. There were no significant differences in COPD severity, treatment received and biochemical parameters between the groups of patients 'at risk of malnutrition' and those 'not at risk of malnutrition'. Length of stay in hospital was longer in patients 'at risk of malnutrition' (median (IQR): 3.5 (2–7.5) vs. 3.0 (1–5), p = 0.048). Overall survival was significantly reduced in patients with 'at risk of malnutrition' compared to those patients 'not at risk of malnutrition' (337 ± 245 vs. 670 ± 292, p < 0.001). Conclusions : Using the MST we found that one-fifths of our hospitalised AECOPD patients are at 'at risk of malnutrition'. Moreover, this cohort of patients had worse outcomes both during and extending beyond hospitalisation compared to patients 'not at risk of malnutrition'. Our study illustrates the need for routine malnutrition screening for hospitalised AECOPD patients because it has implications for potentially reducing morbidity and mortality in COPD.